Survei Sarana Dan Prasarana Cabang Olahraga Bola Voli Se-Kabupaten Tegal (Indonesian Journal for Physical Education and Sport, 2022)
The purpose of this study was to Facilities and Infrastructure for Volleyball Sports in Tegal Regency.. This research is a qualitative, descriptive study using a survey method. data collection techniques through observation, interviews, and documentation. The sample in this study were all volleyball clubs registered with the Tegal Regency PBVSI Management. The results showed that the average infrastructure for volleyball clubs in Tegal Regency was sufficient. For volleyball clubs who feel inadequate in terms of facilities, there is only one club. As for infrastructure, there is 1 volleyball club, the infrastructure is in poor condition, and 1 club is under repair. The results of the study concluded: 1) the availability of infrastructure owned by most clubs was already available; 1 volleyball club had insufficient infrastructure; 2) feasibility, all volleyball clubs were suitable for use; there were 3 clubs with insufficient infrastructure.